Laboratorium Virtual “Gerak Dan Gaya” Tiga Dimensi Menggunakan High Poly - Syam, Supriadi; SAS, Abdillah (JTRISTE, 2022)
This study aims, (1)To design a virtual laboratory "Motion and Style" in science subjects class VIII junior high school based on 3D (2) To implement the virtual laboratory "Motion and Style" in science subjects class VIII junior high school based on 3D (3)To apply the high poly technique on the virtual laboratory "Motion and Style" in science subjects class VIII junior high school. In designing this application, the development of the system used is UML (Unified Modeling Language). While in making applications, the software used in this researce the author uses software, Unity 2020, Visual Studio Code, 3D Studio Max, Autodesk Maya, using high poly techniques. The result of this research is a learning media that can make it easier for students to understand the material presented in learning and can create learning that is not boring, and is able to increase learning motivation in students.